2017
DOI: 10.7554/elife.21526
|View full text |Cite
|
Sign up to set email alerts
|

Lineage commitment of embryonic cells involves MEK1-dependent clearance of pluripotency regulator Ventx2

Abstract: During early embryogenesis, cells must exit pluripotency and commit to multiple lineages in all germ-layers. How this transition is operated in vivo is poorly understood. Here, we report that MEK1 and the Nanog-related transcription factor Ventx2 coordinate this transition. MEK1 was required to make Xenopus pluripotent cells competent to respond to all cell fate inducers tested. Importantly, MEK1 activity was necessary to clear the pluripotency protein Ventx2 at the onset of gastrulation. Thus, concomitant MEK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…Ventx2-depleted embryos developed medullary and extramedullary sensory neurons, the vertebrate homologs of invertebrate proto-NC cells (e.g., the urochordate BTNs) (18,21,22). In addition, we showed that sustained Ventx2 activity during late gastrulation, but not before, enhanced NC identity, suggesting that the developmental function of Ventx2 in promoting NC identity was uncoupled from its role in pluripotent blastula cells (24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Activation of Ventx2 during late gastrulation led to the local expansion of the stem cell marker (pou5f3.1/ oct4) and increased expression of other genes linked to broad developmental potential and reprogramming (tert, tet3, kdm4a, smarcA4, and chd7).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Ventx2-depleted embryos developed medullary and extramedullary sensory neurons, the vertebrate homologs of invertebrate proto-NC cells (e.g., the urochordate BTNs) (18,21,22). In addition, we showed that sustained Ventx2 activity during late gastrulation, but not before, enhanced NC identity, suggesting that the developmental function of Ventx2 in promoting NC identity was uncoupled from its role in pluripotent blastula cells (24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Activation of Ventx2 during late gastrulation led to the local expansion of the stem cell marker (pou5f3.1/ oct4) and increased expression of other genes linked to broad developmental potential and reprogramming (tert, tet3, kdm4a, smarcA4, and chd7).…”
Section: Discussionmentioning
confidence: 75%
“…To date, the architecture of the NB/NC circuitry is a constrained and synapomorphic trait of bilaterians, whereas expression of ventx, nanog, and ved in NB/NC cells is a synapomorphic trait of vertebrates (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Notch1 Mo downregulated other genes important for the ventral program, such as trim29 (Hayes et al, 2007;Cibois et al, 2015;Popov et al, 2017) (Fig. S6H), xk81a1 (Yan et al, 2009;Scerbo et al, 2017) (Fig. S6I) and tfap2a (Luo et al, 2002) (Fig.…”
Section: Notch/csl-dependent Activity Is Higher In the Ventral Sidementioning
confidence: 99%
“…The suppressed expression of organizer-specific genes resulted in a headless phenotype. Studies have shown that Ventx2.2/Xom acts as a Nanog-like pluripotency marker in Xenopus [ 48 , 49 ]. Overexpressed Ventx2.2 stabilizes the cells’ pluripotency and inhibits multiple-cell-lineage commitment during the embryonic development of X. laevis .…”
Section: Introductionmentioning
confidence: 99%